A7.16 Characterisation of changes in lymphocyte subsets in baricitinib-treated patients with rheumatoid arthritis in two phase 3 studies. (24th February 2016) - Emery, P; McInnes, I; Genovese, MC; Smolen, JS; Kremer, J; Dougados, M; Schlichting, DE; Rooney, T; Issa, M; de Bono, S; Macias, WL; Rogai, V; et al.
Abstract : Background and objectives: Baricitinib is an oral, reversible inhibitor of Janus kinase (JAK)1/JAK2 being developed as treatment for patients with RA. Previous studies have shown transient increases in total lymphocyte count within hours of dosing and return to baseline prior to the next dose. We examined changes over time in lymphocyte subsets in RA patients treated with baricitinib or placebo in the phase 3 RA-BUILD and RA-BEACON studies. Materials and methods: Patients had active RA with insufficient response (IR) to conventional synthetic DMARDs (csDMARDs) (RA-BUILD; N=684) or TNF inhibitors (TNFi) (RA-BEACON; N=527). Patients were randomised 1:1:1 to placebo or 2 or 4mg baricitinib QD for 24 weeks. Lymphocyte subsets and natural killer (NK) cells were quantified by flow cytometry at baseline and Week (wk) 4, wk12, and wk24. Total lymphocyte count was measured at each visit. Results: Significant improvements in disease activity were seen for baricitinib versus placebo in both studies. Total lymphocyte increases at wk4 for baricitinib were generally within normal ranges. Change in total lymphocyte count was similar at wk12 and wk24 for baricitinib versus placebo. In RA-BUILD/RA-BEACON, increased T-cells/µL (158.3/22.6 and 124.1/170.7 for 2mg and 4mg, p ≤ 0.05), B-cells/µL (66.7/36.8 and 82.9/74.3 for 2mg and 4mg, p ≤ 0.001), and NK-cells/µL (59.5/36.8 and 46.2/77.0 for 2mg and 4mg, p ≤ 0.01) versus placebo were seen at wk4. Decreased T-cells/µL (wk12= -20.9/0.7 and -87.6/-33.1 for 2mg and 4mg; wk24 = -117.2/-128.1 and -83.4/-53.8 for 2mg and 4mg, p ≤ 0.05) and NK-cells/µL (wk12 = -36.7/-22.0 and -57.0/-22.7 for 2mg and 4mg, p ≤ 0.001 in RA-BEACON; wk24 = -41.2/-45.0 and -53.4/-40.9 for 2mg and 4mg, p ≤ 0.05 in RA-BEACON) and increased B-cells/µL (wk12 = 65.0/49.3 and 75.1/70.2 for 2mg and 4mg, p ≤ 0.001; wk24= 24.3/22.6 and 55.2/65.0 for 2mg and 4mg, p ≤ 0.001 for 4mg) were seen later for baricitinib groups. Changes in other T- and B-cell populations were variable, but generally reflected these patterns. Decreased NK-cell count did not appear to be associated with an increased incidence of infection. Conclusions: Baricitinib produced significant clinical improvements in disease activity in csDMARD-IR and TNFi-IR RA patients. Improvements were accompanied by a variety of changes in lymphocyte counts, predominantly within normal ranges. Similar lymphocyte subset assessments will be available in a long-term extension study.